Pengaruh Pemberian Core Exercise dan Depth Jumps Terhadap Tinggi Lompatan Pada Pemain Basket - Cahyati, Yunisa Ida; , Wijianto, SST.FT, M. Or (2017)
Background: Several component is needed by the basketball players, one of them is lower extremity power that is closely related to the ability to jump. So that basketball players need to get exercises to improve jumping ability which is using core exercise and depth jump Objective: To determine the effect of core exercise on the height of the jump of basketball players, the effect of depth jump on the height of the jump of basketball players, and to determine the different effects of core exercise and depth jump on the height of the jump of basketball players. Benefits: To increase the height of the jump of basketball players by using core exercise and depth jump. Method: Thetypeof research is quasi experiment with the two group pretest-posttest design. The number of samples in this study is 12. Samples are given the core exercise and depth jump for 8 weeks with a 2 times a week of exercise frequency. Statistical analysis using the Wilcoxon test to test the influence and Mann-Whitney Test to test different influences. The height measuring tool is using the Vertical Jump Test leap. Results: After Wilcoxon Test, there is the effect of core exercise to the height of the jump by p-value 0,027. And so does the effect of depth jump after Wilcoxon test by the p-value 0,027. There is a difference between the core exercise influence and depth of the high jump leap in basketball, after Mann-Whitney Test p-value of 0.004 was obtained. Conclusion: There is the effect of core exercise on the height of the jump of basketball players. There is the effect of depth jump on the height of the jump of basketball players. There are different effect between giving core exercise and depth jump on the height of the jump of basketball players, which the core exercise has the better effect on the height of the jump. Keywords: Basketball Players, The Height of The Jump, Core Exercise, Depth Jump